Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1365-313x.2003.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

The plant cyclin‐dependent kinase inhibitor ICK1 has distinct functional domains for in vivo kinase inhibition, protein instability and nuclear localization

Abstract: SummaryInteractor/inhibitor 1 of Cdc2 kinase (ICK1) from Arabidopsis thaliana is the ®rst plant cyclin-dependent kinase (CDK) inhibitor, and overexpression of ICK1 inhibits CDK activity, cell division and plant growth in transgenic plants. In this study, ICK1 and deletion mutants were expressed either alone or as green¯uor-escent protein (GFP) fusion proteins in transgenic Arabidopsis plants. Deletion of the C-terminal 15 or 29 amino acids greatly reduced or completely abolished the effects of ICK1 on the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 68 publications
8
81
0
Order By: Relevance
“…While this work was in progress, a similar intracellular localization of ICK1/KRP1 was reported by analyzing GFP fusions with ICK1/KRP1 (Zhou et al, 2003). Consistent with the report by Zhou and colleagues, we found that YFP fusions with the truncated ICK1/KRP1 109 localized to the nucleus and the cytoplasm in trichomes (Figures 3C, 3G, and 3K; data not shown); a cytoplasmic localization was even more prominent for the GUS:YFP:ICK1/KRP1 109 fusion protein ( Figures 3D, 3H, and 3L).…”
Section: Intracellular Localization Of Ick1/krp1supporting
confidence: 70%
See 2 more Smart Citations
“…While this work was in progress, a similar intracellular localization of ICK1/KRP1 was reported by analyzing GFP fusions with ICK1/KRP1 (Zhou et al, 2003). Consistent with the report by Zhou and colleagues, we found that YFP fusions with the truncated ICK1/KRP1 109 localized to the nucleus and the cytoplasm in trichomes (Figures 3C, 3G, and 3K; data not shown); a cytoplasmic localization was even more prominent for the GUS:YFP:ICK1/KRP1 109 fusion protein ( Figures 3D, 3H, and 3L).…”
Section: Intracellular Localization Of Ick1/krp1supporting
confidence: 70%
“…The limitation in detection of the full-length CKI argues that this domain might regulate the stability of ICK1/KRP1 protein. Consistently, Zhou et al (2003) recently reported that an N-terminally truncated version was present in much higher abundance than the full-length inhibitor.…”
Section: Intercellular Localization Of Ick1/krp1supporting
confidence: 67%
See 1 more Smart Citation
“…This gave rise to the possibility that one of the major targets of a CRL-complex in trichomes could be CDK inhibitors. We and others have previously shown that ICK1/KRP1 is an unstable protein and degraded by the proteasome pathway (32,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 96%
“…On the basis of sequence homology to p27 Kip1 , seven putative CDK inhibitors have been identified in Arabidopsis thaliana, designated as Interactors of Cdc2 Kinase (ICKs) or Kip-related proteins (KRPs). ICK1/KRP1 and ICK2/KRP2 in Arabidopsis were shown to be regulated through the action of the 26S proteasome (Zhou et al, 2003b;Weinl et al, 2005;Jakoby et al, 2006). Although it was recently reported that KRP1 degradation was dependent both on SCF SKP2b and the RING protein RKP (Ren et al, 2008), the physiological roles of these ICK/KRPs and the ubiquitin E3 ligases responsible for their degradation are largely unknown.…”
Section: Introductionmentioning
confidence: 99%